Development Of Learning Aid To Improve The Understanding Of Mathematical Concepts Of Students With Visual Disabilities In Special Schools Part A (Slb A) Pure Work - Ikhsan, Muhibbul; Simanjorang, Mangaratua M; Mukhtar, Mukhtar (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2024)
This study aims to improve the understanding of Mathematics concepts through Geoboard learning media for students with visual disabilities at the SLB-A Karya Murni Education Foundation. This research was conducted at Yayasan Pendidikan SLB-A Karya Murni, which is one of the Junior High Schools (SMP) for students with visual disabilities in Medan City, North Sumatra. In this study using the type of R&D research refers to the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The subjects in this study were seventh grade students of the SLB-A Karya Murni Education Foundation in the 2023/2024 academic year. The product draft in this study has been designed and then validated by 2 experts, namely Material Experts and Media Experts. The results of the initial stage validity test by material experts obtained an average percentage of 46.15% (Less Feasible), Stage two validity test by material experts obtained an average percentage of 88.46% (Very feasible), Stage one validity test by media experts obtained an average percentage of 47.5% (Less feasible), and Stage two validity test by media experts obtained an average percentage of 91.25% (Very Feasible). Understanding of concepts in mathematics learning is obtained from learning activities on flat building material, the results of which are effective assessment with a significant increase in learning outcomes with the category of Nominalised Gain index 0.67 <0.7 classified as (Moderate).This research produces a product in the form of learning media in the form of Geoboard. The Geoboard is feasible to use judging from the percentage obtained in each manufacturing process.